A Case Study of the Impact of Parenting Styles on Independence in Early Childhood - Liyana Liyana; Brigita Puridawaty; Atikah Oktaviani; Baiq Masniati; Popon Widianingsih; Asri Mar'atus Sholihah (Kirana Publisher (KNPub), 2026)
Independence is a crucial aspect of early childhood development that contributes to the formation of self-regulation, decision-making, and responsibility. This study aims to examine the influence of parenting styles on early childhood independence through a case study of Child A, a five-year-old child. The research employed a qualitative approach using a case study method. Data were collected through observation, interviews with parents and teachers, and documentation. The findings indicate that Child A’s independence has not yet developed optimally, particularly in the emotional, behavioral, and value-based aspects. Child A demonstrates a high level of dependence on adult assistance in carrying out daily activities both at home and at school. This condition is closely related to a permissive parenting style characterized by excessive assistance and a lack of consistent responsibility training from an early age. These findings align with Hurlock’s (1993) view that children’s independence develops through opportunities, habituation, and developmentally appropriate support. Therefore, active collaboration between parents and teachers is essential to provide appropriate guidance and opportunities to foster independence in early childhood.